Simultaneous Determination of Methanol, Ethanol and Formic Acid in Serum and Urine by Headspace GC-FID - Bursová, Miroslava; Hložek, Tomáš; Čabala, Radomír (Journal of analytical toxicology, 2015)
A simple, cost-effective headspace gas chromatography (GC) method coupled with GC with flame ionization detection for simultaneous determination of methanol, ethanol and formic acid was developed and validated for clinical and toxicological purposes. Formic acid was derivatized with an excess of isopropanol under acidic conditions to its volatile isopropyl ester while methanol and ethanol remained unchanged. The entire sample preparation procedure is complete within 6 min. The design of the experiment (the face-centered central composite design) was used for finding the optimal conditions for derivatization, headspace sampling and chromatographic separation. The calibration dependences of the method were quadratic in the range from 50 to 5,000 mg/L, with adequate accuracy (89.0–114.4%) and precision (<12%) in the serum. The new method was successfully used for determination of selected analytes in serum samples of intoxicated patients from among those affected by massive methanol poisonings in the Czech Republic in 2012.